Analisis Terhadap Pola Asuh dan Gaya Belajar Siswa Berprestasi - Nur Oktavianti Lestari; Saur M Tampubolon; Yuyun Elizabeth Patras (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
The aim of the study is to describe the correlation among the parenting patterns, learning styles, and students’ achievement at Sekolah Dasar Negeri Papandayan Bogor. The research applied case study model with the approach of qualitative. The procedure of data collection was done by observation, interview, and documentation. The technique of data analysis was done by data reduction, data description, and data verification. The researcher used credibility, transferability, dependability, and conformability tests to validate the data. The subject was a student who has high achievement at Sekolah Dasar Negeri Papandayan Bogor. It was conducted in the odd semester in the year of 2015/2016. The result of the study shows that the parenting pattern of the student’s parents was democratic. The subject showed the combination of learning styles: visual, audio, and kinesthetic (vak learning style), but the most dominant style was visual. The achievement of the student since she was in the first until third grade could be categorized as good; it was proven by the score in her report that was always above the average score of the class. Based on the result above, it can be concluded that a high achieving student cannot be separated from the parenting pattern of being democratic that was always applied by the parents. The most dominant learning style of the high achieving students was visual.